1999
DOI: 10.1046/j.1537-2995.1999.39090938.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of a limited‐donorblood program for neonatal red cell transfusions

Abstract: The limited-donor blood program reduces donor exposure without adversely affecting costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 16 publications
5
26
0
5
Order By: Relevance
“…Previous studies have demonstrated the feasibility of dedicated RBC unit protocols for VLBW infants 7‐10,12‐15 . Reserving blood units to individual patients is achievable, yet widespread application could lead to blood wastage.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the feasibility of dedicated RBC unit protocols for VLBW infants 7‐10,12‐15 . Reserving blood units to individual patients is achievable, yet widespread application could lead to blood wastage.…”
mentioning
confidence: 99%
“…In today's practice, special PLT inventories are frequently maintained for neonatal patients, in attempts to administer transfusions free of CMV, parvovirus B19, WBCs, and bacteria 8 . This may involve the utilization of several blood safety technologies, including serology and nucleic acid testing, leukofiltration, gamma irradiation, and single‐donor apheresis collection instead of whole blood pooling 9‐12 …”
Section: Discussionmentioning
confidence: 99%
“…Several approaches are used today in attempts to provide safe blood components to neonates. Limiting donor exposure is common, but may necessitate single‐donor apheresis 9,10 . Maintaining a supply of well‐characterized donors on hand and splitting donations from single donors are also utilized to provide safer transfusion product to pediatric patients 11,12 .…”
mentioning
confidence: 99%
“…When infants assigned to a unit no longer require RBC transfusions, the remainder of the unit is placed in the general inventory for transfusion to older patients. This plan has been demonstrated to be cost‐effective 17 …”
Section: Transfusing Stored Versus Fresh Rbcsmentioning
confidence: 99%